MEMAHAMI MAKNA HADITS NABI MUHAMMAD SAW SECARA TEKSTUAL DAN KONTEKSTUAL - Ifa Dotus Salimah; Abd Haris (Fakultas Agama Islam Universitas Islam Madura, 2022)
This study aims to understand the meaning contained of hadits Muhammad SAW by describing textual and contextual hadits. The method used in this research is Library Research with variables of textual and contextual hadits. The results of this study are that hadits contains religious messages to be conveyed to the people. To understand these messages, we have to explore the meaning of hadits not only in terms of the hadits’s text, but it is also necessary to understand it contextually by taking into the background, situation and conditions when the hadits was delivered.